Model Organisational Structure of the Kulliyatul Mu’allimin Al-Islamiyah Curriculum Content - Taufik Mukmin; Abdurrahmansyah Abdurrahmansyah; Aflatun Muchtar; Yesi Arikarani (STAI Hubbulwathan Duri, 2023)
This study aims to analyse the design and structure of the content, the type of knowledge that is arranged in the form of subjects, and the content of knowledge in each subject. This research uses qualitative research with phenomenological types, data collected through in-depth interviews, observation and documentation, as well as analysing data through reduction, display and conclusion. The results show that the Kulliyatul Mu’allimin Al-Islamiyah (KMI) content organisation model is